Hegemoni Pemerintah Daerah dalam Pengelolaan Zakat di Kabupaten Bulukumba - Saputro, Eko Rachmat; Utami, Anugerah Mulia; Haris, Umiyati; Hasanah, Nurul Uswatun (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to understand the role of each party in the management of zakat funds, which essentially are funds for the welfare of the community, using a qualitative approach with a descriptive method. This research employs a qualitative approach with a descriptive method. Data collection techniques were carried out through literature studies, observation, and in-depth interviews. The data analysis technique used is qualitative data analysis, which consists of data reduction, data presentation, and drawing conclusions. The analysis results indicate that the hegemony created in the management of zakat in Bulukumba Regency between the local government and BAZNAS (National Amil Zakat Agency) of Bulukumba Regency in this study can be viewed from the process of preparing the RKAT (Annual Work and Budget Plan) conducted annually. From the RKAT preparation process, the BAZNAS of the Regency must always comply with and adhere to the proposals or directives from the local government. Every year, the local government provides input to the Regency BAZNAS in the form of work plans in the fields of education, economy, health, social-humanitarian, as well as advocacy and da'wah. In addition, the local government also targets the amount of budget that must be collected by the Regency BAZNAS each year, and this budget target must be achieved.